The effects of an abusive primary partner on the condom use and sexual negotiation practices of African-American women. - Wingood, G M (1997)
OBJECTIVES: This study examined the consequences of having a physically abusive primary partner on the condom use and sexual negotiation practices of young African-American women. METHODS: Interviews were conducted with 165 sexually active African-American women aged 18 through 29 in San Francisco, Calif. RESULTS: Women in abusive relationships were less likely than others to use condoms and were more likely to experience verbal abuse, emotional abuse, or threats of physical abuse when they discussed condoms. They were more fearful of asking their partners to use condoms, worried more about acquiring the human immunodeficiency virus (HIV), and felt more isolated than did women not in abusive relationships. CONCLUSIONS: HIV prevention programs for women should address domestic violence prevention strategies.